Knowledge, Attitude, and Practices Associated With COVID-19 Among Healthcare Workers in Hospitals: A Cross-Sectional Study in Saudi Arabia - Almohammed, Omar A.; Aldwihi, Leen A.; Alragas, Adel M.; Almoteer, Ali I.; Gopalakrishnan, Shivkumar; Alqahtani, Nasser M. (Frontiers in Public Health, 2021)
Lack of knowledge among healthcare workers (HCWs) about infectious diseases leads to delayed diagnosis of new cases, spread of infection and poor infection control practices. Therefore, HCWs based in hospitals must be equipped with good knowledge about the pathogen and disease to put up a robust fight against the virus. The aim of this study was to assess HCWs’ knowledge, attitude and practices (KAP) about coronavirus disease 2019 (COVID-19) at multiple public and private hospitals in Riyadh, Saudi Arabia. A cross-sectional, online questionnaire-based study was conducted between July and August of 2020. Logistic regression was used to investigate differences in the level of KAP among different participants. A total of 510 HCWs in hospitals completed the questionnaire. Only two-thirds of the participants (67.8%) had adequate knowledge about COVID-19, 72.2% of participants had a positive attitude toward COVID-19 and 80.2% of participants were practicing appropriately most of the time. Poor KAP was associated with low education level. Females had better knowledge and attitude, whereas males were more likely to practice appropriately most of the time. Notably, participants from the nursing profession demonstrated less favorable attitude compared with medical staff from other professions but that did not prevent them from being the best when it comes to applying appropriate practices. The inadequate level of KAP among HCWs with the continuation of the pandemic and the possibility of a second wave demonstrates the need for continuous COVID-19-specific infection control training and emotional wellbeing supporting programs, especially for HCWs with low education level.